“Respuesta agronómica del cultivo de arroz (Oryza sativa L.), a la aplicación de fertilizantes con Silicio y Magnesio, en condiciones de secano”. - Zamora Valero, Cristhian Miguel (2019)
SUMMARY The present experimental work was carried out on the grounds of the Cooperativa "San Antonio", owned by Mr. Gilberto Federico Zamora Vera, located at km. 1.0 via Baba - Bejucal Island, located at the geographic coordinates of 197165.89 UTM South Latitude, 351695.02 West Longitude, with a height of 8 masl. The area has a tropical climate, with an average annual temperature of 25.6 ° C, annual precipitation 1,730 mm, relative humidity of 82%. The soil is of alluvial origin, flat topography, clay loam texture, drainage and regular fertility. The rice seed variety Iniap FL 1480 "Cristalino" was used. The treatments consisted of the two doses of Silicon (5, 10 kg / ha) and three doses of Magnesium (10, 20, 30 kg / ha) applied at 15 and 30 days after sowing. The experimental design "Random blocks" with 3 repetitions was used. The variables evaluated were subjected to the analysis of variance and to determine the statistical difference between the means of the treatments, the Tukey test will be applied at 95% probability. The tasks of land preparation, sowing, fertilization, irrigation, weed control, insect control, pests and diseases, and harvesting were carried out in the crop. To determine the results, the variables of plant height, number of tillers and panicles / m2, length of panicles, grains per panicles, weight of 1000 seeds, yield per hectare and economic analysis were evaluated. For the results obtained it was determined that an excellent response of the rice crop, variety Iniap FL 1480 "Cristalino", to the complementary fertilization with Silicon and Magnesium was presented; agronomic traits such as plant height, tillers and panicles per square meter, panicle length, grains per panicle and 1000 grain weight obtained excellent response with application of 10 kg / ha Silicon + 20 kg / ha of magnesium at 15 and 30 days after sowing; the greater yield of the grain and greater net benefit reached the use of 10 kg / ha of Silicon + 20 kg / ha of Magnesium with 6033.3 kg / ha and $ 565.1. Keywords: rice, fertilization, magnesium, micronutrients, silicon.